Evaluation of the Implementation of Simon's Levers of Control to Achieve Strategic Objectives at PT ABC - Putri Ayuningtyas Kusumawati; Hilda Rossieta (E-Jurnal Akuntansi, 2025)
This study aims to evaluate the implementation of Simon's Levers of Control at PT ABC to assess how effectively the company is achieving its strategic objectives. This study was conducted using a case study method based on evaluation and descriptive qualitative methods. Data was collected through semi-structured interviews and document analysis. The focus of this study is PT ABC, a company operating within the telecommunications sector. The results of the study show that the company has had and implemented the entire control system, but there are still weaknesses in the diagnostic control system such as plans that cannot be executed on the OSP FO Backbond project which causes the project to experience a delay from the target completion of the work. In terms of the boundary system, there is an increase in violations of the code of ethics when compared to the previous year.